2018
DOI: 10.1016/j.bbagen.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Morphine, a potential inhibitor of myeloperoxidase activity

Abstract: Morphine is an opioid alkaloid commonly used in clinical practice for its analgesic properties. The phenolic hydroxyl group of that phenanthrene derivative is pivotal for binding to opioid receptors but it may also be responsible for the antioxidant behavior of morphine reported in several in vitro experiments. In this study, we assessed the effect of morphine on myeloperoxidase (MPO), a hemic enzyme from azurophilic granules of polymorphonuclear neutrophils involved in the production of cytotoxic and microbic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In fact, MPO activity was found to be reduced in lung tissue, relative to the controls, after intravenous administration of 20 mg/kg tramadol in a rat model of ischemia-reperfusion [74]. Interestingly, morphine has been reported as an MPO inhibitor [75], for which a similar effect might be anticipated for other structurally related opioids. Still, tissue quantification of MPO activity would add information on this aspect, since an increase in its levels was reported in rat brain tissue following a 9-week daily treatment with 22.5 to 90 mg/kg tramadol [68].…”
Section: Repeated Administration Of Tramadol and Tapentadol Leads Maimentioning
confidence: 85%
“…In fact, MPO activity was found to be reduced in lung tissue, relative to the controls, after intravenous administration of 20 mg/kg tramadol in a rat model of ischemia-reperfusion [74]. Interestingly, morphine has been reported as an MPO inhibitor [75], for which a similar effect might be anticipated for other structurally related opioids. Still, tissue quantification of MPO activity would add information on this aspect, since an increase in its levels was reported in rat brain tissue following a 9-week daily treatment with 22.5 to 90 mg/kg tramadol [68].…”
Section: Repeated Administration Of Tramadol and Tapentadol Leads Maimentioning
confidence: 85%
“…However, the major antioxidant defense enzymes have been studied in response to opioid exposure: SOD activity has been shown to be decreased in human erythrocytes [ 121 ], plasma [ 12 ], and sperm [ 122 ], as well as in rat cerebrum [ 123 ], hippocampus [ 124 ], and liver [ 125 ]; CAT has been shown to be decreased in human erythrocytes [ 121 ] and plasma [ 12 ], as well as rat cerebrum [ 123 ] and livers [ 125 ]; and GPx has been shown to be decreased in human plasma [ 12 ] and sperm [ 122 ], as well as rat whole brain [ 126 ], cerebrum [ 123 ], and hippocampus [ 124 ], after opioid exposure. Few studies have looked at alternate redox enzymes, but have revealed increases in thioredoxin [ 107 ] as well as decreases in peroxiredoxin [ 127 ] and myeloperoxidase [ 128 ].…”
Section: Opioids Vitamin C and Direct Oxidative Stress Modulationmentioning
confidence: 99%
“…Measurement of the peroxidase activity of MPO was performed with a classical enzymatic assay and the SIEFED assay as described by Nyssen et al (37). The MPO solution was prepared with purified equine or human MPO in the dilution buffer (20 mM PBS, pH 7.4, with 5 g/L BSA and 0.1% Tween-20).…”
Section: Measurement Of Mpo Activitymentioning
confidence: 99%
“…This assay was performed on the human MPO as its crystallographic (X-ray) structure is wellknown in contrast to that of equine MPO (39). The potential inhibitory effect of juglone was docked in the heme pocket using the GOLD program as described by Nyssen et al (37). Five runs have been performed with the aim to determine the most frequent solutions and ensure their reproducibility.…”
Section: Docking Of Mpo-juglonementioning
confidence: 99%